JHEA, Volume 15, n°1, 2017 - Full Issue - system, journal (Journal of Higher Education in Africa, 2021)
Contents Editorial: Building the Vision – Higher Education and Quality Assurance in East Africa Pammla Petrucka........................................1 Why Measurement Matters: The Learning Outcomes Approach – A Case Study from Canada Sarah Brumwell, Fiona Deller & Alexandra MacFarlane.....................................5 Quality Issues in Kenya’s Higher Education Institutions Rosemary Kagondu & Simmy M. Marwa..............................23 University Students Learning Experiences: Nuanced Voices from Graduate Tracer Study Omar Badiru Egesah & Mary Nyawira Wahome .................................43 Institutional Constraints Affecting Quality Assurance Processes in Tanzania’s Private Universities Samson John Mgaiwa & Johnson Muchunguzi Ishengoma..................................57 Broadening Perceptions and Parameters for Quality Assurance in University Operations in Uganda Frederick Kakembo & Rita Makumbi Barymak..........................69 Student Evaluation of Teaching: Bringing Principles into Practice Geoff Tennant & Tashmin Khamis.........................89 Reflections on an Innovative Mentoring Partnership Facilitators and Inhibitors to Success in Faculty Development Tashmin Khamis & Marilyn Chapman.......................105 Quality Assurance Self-assessment: A Catalyst at Aga Khan University Tashmin Khamis & Khairunnisa Dhamani...........................................125 Assessing the Cognitive Domain through MCQs: Critical to Quality Assurance in Higher Education Khairunnisa Aziz Dhamani & Zeenatkhanu Kanji..................................135